2018
DOI: 10.1080/07391102.2017.1413424
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics potentiating potential of catharanthine against superbug Pseudomonas aeruginosa

Abstract: Multidrug resistance (MDR) put an alarming situation like preantibiotic era which compels us to invigorate the basic science of anti-infective chemotherapy. Hence, the drug resistant genes/proteins were explored as promising drug targets. Keeping this thing in mind, proteome of Pseudomonas aeruginosa PA01 was explored, which resulted in the identification of tripartite protein complexes (MexA, MexB, and OprM) as promising drug target for the screening of natural and synthetic inhibitors. The purpose of present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…By using a ramAp : gfp reporter construct, which responds to efflux inhibition without addition of antibiotics, and regardless of the method of inhibition, we developed a high-throughput screen that successfully identified inhibitors of multidrug efflux from two libraries of compounds. Three of the identified compounds from the Prestwick library have been previously identified as efflux inhibitors in bacteria ( 33 35 ), thus validating the screen, and a further 40 from the Roche library were characterized as inhibitors of multidrug efflux in Gram-negative bacteria. A further four of the identified compounds from the Prestwick library have been reported to potentiate antibiotic activity but without a mechanism being identified ( 18 , 36 ), while four other compounds identified by our screen are known to inhibit transport in eukaryotic cells ( 32 , 37 39 ).…”
Section: Discussionmentioning
confidence: 65%
“…By using a ramAp : gfp reporter construct, which responds to efflux inhibition without addition of antibiotics, and regardless of the method of inhibition, we developed a high-throughput screen that successfully identified inhibitors of multidrug efflux from two libraries of compounds. Three of the identified compounds from the Prestwick library have been previously identified as efflux inhibitors in bacteria ( 33 35 ), thus validating the screen, and a further 40 from the Roche library were characterized as inhibitors of multidrug efflux in Gram-negative bacteria. A further four of the identified compounds from the Prestwick library have been reported to potentiate antibiotic activity but without a mechanism being identified ( 18 , 36 ), while four other compounds identified by our screen are known to inhibit transport in eukaryotic cells ( 32 , 37 39 ).…”
Section: Discussionmentioning
confidence: 65%
“…Cumin demonstrated antimicrobial activity on its own and also resistance modulation properties against MRSA by inhibiting LmrS efflux pump [ 155 ]. Plant molecules inhibiting the ethidium bromide efflux pump (EtBr) have also been found: 1′-S-1′-acetoxyeugenol acetate inhibits it in Mycobacterium smegmatis [ 165 ], catechol and catharanthine inhibits it in P. aeruginosa [ 166 , 167 ] and galotannins inhibit it in MDR uropathogenic E. coli [ 168 ]. The Yojl efflux pump of MDR E. coli has been shown to be inhibited by molecules such as 4-hydroxy—tetralone, ursolic acid and its derivatives [ 169 ] and lysergol [ 170 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dwivedi et al [23] indicated that alkaloid chanoclavine isolated from Ipomoea muricata potentiates the activity of tetracycline against MDR clinical E. coli isolate, possibly by inhibiting drug efflux and downregulating the expression of drug transporters. In addition, catharanthine isolated from the leaves of flowering plant Catharanthus roseus has been shown to potentiate the activity of tetracycline, possibly due to the inhibition of the efflux pumps in P. aeruginosa [24]. 3,4-Dibromopyrrole-2,5-dione, a bacterial halogenated metabolite, is an effective EPI against bacterial strains that overexpress AcrB-TolC, MexAB-OprM, and MexXY-OprM [72].…”
Section: Resultsmentioning
confidence: 99%
“…EPIs may affect the function of efflux pumps by (i) regulating the expression of the pump, (ii) inhibiting the functional assembly of the membrane transporter complex involved in drug efflux, (iii) interfering with the energy required for active drug transport, and (iv) inhibiting drug transport via competitive/noncompetitive binding or by physically blocking the efflux channel [15]. Several classes of EPIs, including antibiotic (tetracyclines, aminoglycosides, and fluoroquinolones) analogs [1618], amide derivatives (aromatic nitrogen-containing compounds) [19, 20], indoles [21], alkaloids [2224]), flavonoids [25, 26], aromatic ketones [27], terpenes [28], and oligosaccharides [29], have been reported to date. Several well-known EPIs, such as phenylalanine-arginine β -naphthylamide (PA β N) [30], carbonyl cyanide m -chlorophenylhydrazone (CCCP) [31], verapamil [32], and reserpine [33], have seen limited clinical use and development owing to their toxicity [14].…”
Section: Introductionmentioning
confidence: 99%